The pharmacodynamics of diphenhydramine-induced drowsiness and changes in mental performance - Gengo, F; Gabos, C; Miller, J K (Clinical pharmacology and therapeutics, 1989)
The time course of diphenhydramine concentrations and effects on both mental performance and subjective feelings of drowsiness were assessed in 15 healthy men. Subjects received single oral doses of diphenhydramine, 50 mg, and placebo in this double-blind crossover study. Diphenhydramine plasma concentrations and central nervous system actions were assessed for 24 hours after each treatment. Cognitive impairment was assessed with an automobile driving simulator and digit symbol substitution scores, whereas drowsiness was self-assessed on a visual analog scale. Diphenhydramine produced significant feelings of drowsiness for up to 6 hours after the dose, whereas significant mental impairment was apparent for only 2 hours. Despite the difference in duration of these effects, drowsiness and mental impairment have parallel slopes when effects are related to diphenhydramine concentrations. These data suggest that although the apparent diphenhydramine concentration thresholds to produce drowsiness are lower (30.4 to 41.5 ng/ml) than those needed to produce mental impairment (58.2 to 74.4 ng/ml), these effects have profiles consistent with their being manifestations of the same pharmacologic effect.